A new model of exercise referral scheme in primary care: is the effect on adherence to physical activity sustainable in the long term? A 15-month randomised controlled trial. Issue 3 (3rd March 2018) - Martín-Borràs, Carme; Giné-Garriga, Maria; Puig-Ribera, Anna; Martín, Carlos; Solà, Mercè; Cuesta-Vargas, Antonio I
Abstract : Introduction: Studies had not yet overcome the most relevant barriers to physical activity (PA) adherence. An exercise referral scheme (ERS) with mechanisms to promote social support might enhance adherence to PA in the long term. Setting: A randomised controlled trial in 10 primary care centres in Spain. Objective: To assess the effectiveness of a primary care-based ERS linked to municipal resources and enhancing social support and social participation in establishing adherence to PA among adults over a 15-month period. Participants: 422 insufficiently active participants suffering from at least one chronic condition were included. 220 patients (69.5 (8.4) years; 136 women) were randomly allocated to the intervention group (IG) and 202 (68.2 (8.9) years; 121 women) to the control group (CG). Interventions: The IG went through a 12-week standardised ERS linked to community resources and with inclusion of mechanisms to enhance social support. The CG received usual care from their primary care practice. Outcomes: The main outcome measure was self-report PA with the International Physical Activity Questionnaire and secondary outcomes included stages of change and social support to PA practice. Data collection: Participant-level data were collected via questionnaires at baseline, and at months 3, 9 and 15. Blinding: The study statistician and research assessors were blinded to group allocation. Results: Compared with usual care, follow-up data at month 15 for the ERS group showed a significant increase of self-reported PA (IG: 1373±1845 metabolic equivalents (MET) min/week, n=195; CG: 919±1454 MET min/week, n=144; P=0.009). Higher adherence (in terms of a more active stage of change) was associated with higher PA level at baseline and with social support. Conclusions: Prescription from ordinary primary care centres staff yielded adherence to PA practice in the long term. An innovative ERS linked to community resources and enhancing social support had shown to be sustainable in the long term. Trial registration number: NCT00714831 ; Results.